Some parameters of ’nonsense’ orientation in Mallard - Matthews, G V T (Wildfowl, 1967)
Relay observers, connected by radio, were established on a north-west line to discover how long Mallard continued to fly in that direction after release. The observers provided positive data on 493 birds. Cross-fixes established the distances to which Mallard can be followed visually, and their straight line flying speeds. After being lost to sight by the liberator the birds’ flight became increasingly undirected and within four miles their general orientation had ceased to have any relation to that which they had initially. The great majority would have landed within twenty minutes. ’Nonsense’ orientation is thus a short-lived affair.